Studies on Edible Oil Separation in Water Stagnant Emulsion Under Non-Uniform Pulse DC Electric Field - Esfandian, Hossein; Ghorbani, Mohsen; Katal, Reza (Asian Journal of Chemistry, 2010)
In this study, non-uniform electric field in electrophoresis for removing and coagulating edible oil particles is used. The effects of temperature, time and voltage for outputs were examined. Turbidity measurements were investigated by spectrophotometer. Under laboratory condition, voltage of 3000 V and temperature of 35 ºC, nephelometric turbidity unit (NTU) reached 1098.56- 257.02, which suggest that the separation efficiency is 77 %.